Learning through WhatsApp during the COVID-19 pandemic : a case study - Mheidly, Nour; Graña, Geisel García; Tayie, Sally Samy (Penerbit Universiti Kebangsaan Malaysia, 2021)
The COVID-19 pandemic forced lockdowns that severely affected the educational sector. The necessary shift to online learning was hindered in countries that lack communication technologies. In addition, the inadequate media and information literacy among educators and students alike exposed deficiencies in disaster preparedness. This resulted in the use of commonly used applications, such as WhatsApp, as a learning platform. We hereby present the learning experience of a mathematics class of the 10th grade through WhatsApp in a Lebanese public school. After analysis, we assess the initiative using the Rubric for eLearning Tool Evaluation. Although WhatsApp, as a learning tool, was functional, accessible, and technically effective, it hindered the learning experience with the lack of social, teaching, and cognitive presence. We offer our insights and recommendations on improving the learning and communication experience as we continue to navigate the current and any future pandemic.